Seed morphology and genetic parameters on Eucalyptus urophylla x grandis seedlings development - Camilo, Vinícius de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Is known that mostly of the Eucalyptus genus has a mixed mating system. The distinction of which seed is selfed or crossed is important for breeding programs, for either acquiring pure lines or avoiding inbreeding depression while crossin them. Thus, we tried to establish an easier method for distinguishing selfing from crossing by exploring both morphological traits of seeds (such as appearance, size and weight) and early development of seedlings (in form of germination percentage and height at different ages). Also, we tested the effect of monoclonal fields on the induction of self-fertilization. Seeds was collected from the middle of fields of four commercial clone types of E. urophylla x grandis and submitted to a screening based on three procedures: (i) manual selection by its physical integrity, (ii) granulometric sieves for size and (iii) seed blowers for weight. All categories were placed on a germination test and the seedlings had their height measured at 2nd, 4th, and 6th month since germination. Single Sequence Repeat (SSR) genetic markers were used to estimate clones crossing rate and determine offspring heterozygosity. Germination rates varied significantly between clones and morphological groups of seeds, as did heights between categories in the first measurement; however, the second and third measurements did not shown difference. There was a large variation of selfing rate among clones. Nonetheless, there was no correlation between any seed morphological trait or size of seedling with inbreeding coefficient (f) incidence. The results are discussed in terms of implications for usage of morphological traits for the obtention of inbred individuals for the species and higher quality seedlings.

Sabe-se que a maior parte do gênero Eucalyptus possui um sistema de reprodução misto. A distinção entre sementes autofecundadas e cruzadas é importante para programas de melhoramento, seja para obter linhagens puras ou evitar a depressão endogâmica durante o cruzamento. Assim, tentamos estabelecer um método mais fácil para distinguir a autofecundação do cruzamento, explorando características morfológicas das sementes (como aparência, tamanho e peso) e o desenvolvimento inicial das plântulas (na forma de porcentagem de germinação e altura em diferentes idades). Também testamos o efeito de campos monoclonais na indução da autofecundação. Sementes foram coletadas do meio de campos de quatro tipos comerciais de clones de E. urophylla x grandis e submetidas a uma triagem baseada em três procedimentos: (i) seleção manual por sua integridade física, (ii) peneiras granulométricas para tamanho e (iii) sopradores de sementes para peso. Todas as categorias foram colocadas em um teste de germinação e as plântulas tiveram sua altura medida no 2º, 4º e 6º mês após a germinação. Marcadores genéticos de repetição de sequência única (SSR) foram utilizados para estimar a taxa de cruzamento de clones e determinar a heterozigosidade da prole. As taxas de germinação variaram significativamente entre clones e grupos morfológicos de sementes, assim como as alturas entre categorias na primeira medição; no entanto, a segunda e a terceira medições não mostraram diferença. Houve uma grande variação na taxa de autofecundação entre os clones. No entanto, não houve correlação entre qualquer característica morfológica da semente ou tamanho da plântula com a incidência do coeficiente de endogamia (f). Os resultados são discutidos em termos de implicações para o uso de características morfológicas para a obtenção de indivíduos endogâmicos para a espécie e mudas de maior qualidade.
Morfologia de sementes e parâmetros genéticos no desenvolvimento de mudas de Eucalyptus urophylla x grandis
Keywords: Eucalyptus; Seeds; Selfing; Induction